Self-medication among students of a higher education institution in Goiás - Alves, Tarine de Araújo; Malafaia, Guilherme (ABCS Health Sciences, 2014)
Introduction: Self-medication has been considered a growing practice nowadays. Objective: To identify aspects of the prevalence of self-medication and what medications are commonly used among students from different higher-level courses at the Instituto Federal Goiano, Campus Urutaí, Brazil. Methods: A cross-sectional observational study in which 160 students answered a self-administered questionnaire containing diversified questions. For data analysis, we used descriptive statistics using Microsoft Excel software. Results: Of all participants, 52.4% were male and the average age was 21.5 years old. The overall prevalence of self-medication was 68.3%. Factors leading academics of the investigated institution using non-prescription medicines are mainly guidance for selfmedication stemmed from sources of information related to medical signs and/or symptoms related disorders that cause headache, fever and body ache. Furthermore, it was found that students of different higher education courses from the investigated institution have a similar self-medication profile, with a prevalence of analgesics, antipyretics, antibiotics and anti-inflammatories (uncontrolled and controlled drugs). They also showed little knowledge about the adverse effects or contraindications of the consumed drug. Conclusion: Selfmedication is a serious and important issue in the context of higher education of the Instituto Federal Goiano, Campus Urutaí, and it is not only restricted to medical and/or biological areas. Therefore, it is necessary to carry out actions/activities that contribute to the rational use of medicines.